2010
DOI: 10.1074/jbc.m110.168211
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Function Correlation of G6, a Novel Small Molecule Inhibitor of Jak2

Abstract: Somatic mutations in the Jak2 protein, such as V617F, cause aberrant Jak/STAT signaling and can lead to the development of myeloproliferative neoplasms. This discovery has led to the search for small molecule inhibitors that target Jak2. Using structure-based virtual screening, our group recently identified a novel small molecule inhibitor of Jak2 named G6. Here, we identified a structure-function correlation of this compound. Specifically, five derivative compounds of G6 having structural similarity to the or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Jak2/STAT signaling is known to positively regulate cell growth by directly increasing expression of the anti-apoptotic marker, Bcl-xL, via STAT-binding elements located in its proximal promoter region (26,27). In a recently published work, we reported that G6 inhibits HEL cell growth via the down-regulation of Bcl-xL and this correlates with significantly reduced phospho-STAT5 levels (28). Furthermore, we showed that G6 treatment of HEL cells results in upregulation of pro-apoptotic Bim, and cleavage of pro-apoptotic Bid, from its inactive precursor to its active form (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jak2/STAT signaling is known to positively regulate cell growth by directly increasing expression of the anti-apoptotic marker, Bcl-xL, via STAT-binding elements located in its proximal promoter region (26,27). In a recently published work, we reported that G6 inhibits HEL cell growth via the down-regulation of Bcl-xL and this correlates with significantly reduced phospho-STAT5 levels (28). Furthermore, we showed that G6 treatment of HEL cells results in upregulation of pro-apoptotic Bim, and cleavage of pro-apoptotic Bid, from its inactive precursor to its active form (28).…”
Section: Discussionmentioning
confidence: 99%
“…In a recently published work, we reported that G6 inhibits HEL cell growth via the down-regulation of Bcl-xL and this correlates with significantly reduced phospho-STAT5 levels (28). Furthermore, we showed that G6 treatment of HEL cells results in upregulation of pro-apoptotic Bim, and cleavage of pro-apoptotic Bid, from its inactive precursor to its active form (28). In our work here, we show that G6 treatment results in reduced STAT5 phosphorylation within HEL cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…16 We also demonstrated that the stilbene core structure of G6 is essential for its activity as a Jak2 inhibitor, in vitro and ex vivo . 17 Here, we further examined the structure of G6 to determine if structural modifications of the compound could enhance its Jak2 inhibitory potential. We hypothesized that the structure of G6 could be minimized in order to enhance its Jak2 inhibitory potential and that maintaining the para -hydroxyl orientation is required for Jak2 inhibition.…”
mentioning
confidence: 99%
“…NB13 and NB15 showed interactions very similar to those of the parent compound, G6. 17 These include hydrogen bonds with residues in the hinge region, the activation loop, and the catalytic loop. NB4 and NB6 showed hydrogen bond interactions with several residues, but lacked any interactions with the critical hinge region residues, Glu930 or Leu932.…”
mentioning
confidence: 99%
See 1 more Smart Citation